2007
DOI: 10.1016/j.rmed.2007.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle dysfunction in patients with idiopathic pulmonary arterial hypertension

Abstract: Dyspnea and exercise limitation are common in patients with idiopathic pulmonary arterial hypertension (IPAH). Recently, a reduction in inspiratory and expiratory muscle strength has been observed in IPAH. However, it has not been investigated whether this respiratory muscle weakness might be part of a general muscle dysfunction as observed in congestive left heart failure. Therefore, in 24 consecutive IPAH patients (16 female; age 58.7+/-16.2; WHO class II-III; systolic pulmonary artery pressure during echoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 24 publications
1
88
1
4
Order By: Relevance
“…65 More recently, Bauer et al studied forearm muscle function in 24 patients with IPAH and found abnormalities that were qualitatively similar to those in patients with LV failure. 75 In addition, the reduction in skeletal muscle strength was paralleled by respiratory muscle dysfunction in these patients. 76 And further support of this concept comes from a study that has demonstrated a marked improvement in exercise capacity in patients with severe PAH following an exercise rehabilitation program, 27 far greater than the effects from vasodilator therapy, but analogous to the observations that have been made in LV failure.…”
Section: Skeletal Muscle In Patients With Phmentioning
confidence: 87%
“…65 More recently, Bauer et al studied forearm muscle function in 24 patients with IPAH and found abnormalities that were qualitatively similar to those in patients with LV failure. 75 In addition, the reduction in skeletal muscle strength was paralleled by respiratory muscle dysfunction in these patients. 76 And further support of this concept comes from a study that has demonstrated a marked improvement in exercise capacity in patients with severe PAH following an exercise rehabilitation program, 27 far greater than the effects from vasodilator therapy, but analogous to the observations that have been made in LV failure.…”
Section: Skeletal Muscle In Patients With Phmentioning
confidence: 87%
“…More recently, several reports suggested muscle dysfunction in patients with pulmonary arterial hypertension [14][15][16]. Mechanisms are still unclear, but it can be speculated that inactivity of the skeletal muscles, together with a decreased cardiac output leading to a reduced oxygen transport to the skeletal muscles, trigger morphological changes, such as muscle atrophy, fibre type switching and reduced aerobic capacity [18].…”
Section: Training Improved Endurance Capacitymentioning
confidence: 99%
“…Respiratory muscle dysfunction was found in two studies, both by voluntary and nonvoluntary techniques [14,15]. More recently, forearm muscle dysfunction has been reported in these patients [16]. In a pilot study, examining voluntary strength of the respiratory, forearm and quadriceps muscles in iPAH patients, specific quadriceps muscle dysfunction has been found [17].…”
mentioning
confidence: 95%
“…In addition, muscle strength may be reduced in patients with pulmonary hypertension compared with control subjects [17]. A delayed recovery in TLCO could be considered the consequence of major surgery in the early period after PEA and of the vessels remodelling before surgery in the nonobstructed segments of the lungs in the later follow-up.…”
Section: Determinants Of Exercise Capacity After Peamentioning
confidence: 99%